L-Fuzzy Congruences and L-Fuzzy Kernel Ideals in Ockham Algebras. (19th June 2021) - Alemayehu, Teferi Getachew; Engidaw, Derso Abeje; Addis, Gezahagne Mulat
Abstract : In this paper, we study fuzzy congruence relations and kernel fuzzy ideals of an Ockham algebra A, f, whose truth values are in a complete lattice satisfying the infinite meet distributive law. Some equivalent conditions are derived for a fuzzy ideal of an Ockham algebra A to become a fuzzy kernel ideal. We also obtain the smallest (respectively, the largest) fuzzy congruence on A having a given fuzzy ideal as its kernel.